Give Me Your Tired and Your Poor: Impact of a Large-Scale Amnesty Program for Undocumented Refugees - Dany Bahar; Ana María Ibá\~nez; Sandra V. Rozo (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Between 2014 and 2020 over 1.8 million refugees fled from Venezuela to Colombia as a result of a humanitarian crisis, many of them without a regular migratory status. We study the short- to medium-term labor market impacts in Colombia of the Permiso Temporal de Permanencia program, the largest migratory amnesty program offered to undocumented migrants in a developing country in modern history. The program granted regular migratory status and work permits to nearly half a million undocumented Venezuelan migrants in Colombia in August 2018. To identify the effects of the program, we match confidential administrative data on the location of undocumented migrants with department-monthly data from household surveys and compare labor outcomes in departments that were granted different average time windows to register for the amnesty online, before and after the program roll-out. We are only able to distinguish negative albeit negligible effects of the program on the formal employment of Colombian workers. These effects are predominantly concentrated in highly educated and in female workers.
Keywords: F22; O15; R23; 330; migration; work permit; labor markets; amnesties